Methods for the biological control of Potato Cyst Nematodes - Adamou, Andri (Department of Agricultural Science, Biotechnology and Food Science, Faculty of Geotechnical Science and Environmental Managment, Cyprus University of Technology, 2020)
A demonstration movement has been developing in recent years environmental sensitivity, emphasizing the application of coastal agriculture, which can protect biodiversity and ecological balance, and promote the production of quality products. That is why the shift from conventional agriculture to organic farming is attempted. Based on these data, this work will analyze the role of the biological treatment of potato cyst nematodes. In the social sector, the role of biological farming recognized as a safe method of food production that responds to consumer concerns. This present review study is an attempt to report and explain the usefulness of the biological control methods of potato cyst nematodes (PCN). The first chapter demonstrates an overview of PCN. Recognizing the biological cycle, certain behavioral characteristics, and the symptoms of PCN, helps to understand the use of biological control in plants. The second chapter analyzes some of the biological control methods, while the third chapter adds some alternative methods of biological control of nematodes.
Keywords: Potato cyst nematodes; Globodera rostochiensis; Globodera pallida; Biological control; Biocontrol